Study of nutrition in poor adults Lima - Ortíz Torrelio, Héctor (1954)
In the dietary study 100 subjects of the poor class of Lima, who go to outpatient hospital "2 de Mayo" and "Arzobispo Loayza" We have found the following results: In 91% of cases there is a decrease weight in relation to height. On clinical examination designed to uncover signs of under-nutrition, 42% have been found lesions ariboflavinosis net and none clinical signs of hypoproteinemia or frank deficiency of ascorbic acid; in 48%, signs of pale skin and mucous membranes, which is related to low levels of hemoglobin found in the laboratory. There is a close relationship between speed and accelerated cases of vitamin C. From the data found can conclude that the subjects have mostly overt signs of under-nutrition; often accentuated, which may partially be due to pathological processes suffering; the rest would be due to a poor diet and vitamin protective elements. The present work together with those performed at the Institute of Biochemistry and Nutrition of our faculty; we will give an overview of the physiological reality in the different social classes of our country.